CLAmp‐seq: A Novel Amplicon‐Based NGS Assay with Concatemer Error Correction for Improved Detection of Actionable Mutations in Plasma cfDNA from Patients with NSCLC. Issue 4 (13th August 2019) - Wang, Lin; Hu, Xiaomeng; Guo, Qiaomei; Huang, Xia; Lin, Chia‐Hui; Chen, Xiao; Li, Min; Yao, Qianqian; Zhou, Qianjun; Wang, Jianmin; Lin, Shengrong; Zhao, Grace; et al.
Abstract: High‐throughput sequencing of circulating cell‐free DNA (cfDNA) is critical for targeted therapy selection and monitoring in non‐small cell lung cancer (NSCLC) patients. However, low quantities of cfDNA in the blood and assay artifacts limit the sensitivity and specificity of next‐generation sequencing (NGS) test. This study develops a novel amplicon‐based NGS technology, CLAmp‐seq (c ircular l igation a mplification and sequencing), with a concatemer‐based error correction strategy, which effectively removes polymerase errors from the first round of amplification. Analytical validation shows median detection rate of 100% at a mutant allele frequency (MAF) of 0.1% for 20 ng of input. The assay achieves 99.8% and 99.5% concordance of repeatability and reproducibility for 0.1% MAF, respectively, and both 100% for 0.5% MAF cfDNA standards. A comparative analysis of 134 NSCLC patient plasma samples demonstrates strong concordance (97.4%) and linearity ( R 2 = 0.95) between the CLAmp‐seq NGS readouts and droplet digital PCR (ddPCR) results. The detection of mutants in cfDNA obtained from pretreatment plasma samples shows 94.8% concordance with tissue genotyping results. No mutation is detected in noncancerous control samples. It shows that CLAmp‐seq NGS assay can offer an easy‐to‐use, fast, and accurate molecular diagnostic tool with multiplex capacity that is well‐suited for clinical in vitro diagnosis. Abstract : Ultrasensitive detection of low mutant allele frequency (MAF) variants in plasma is achieved by a novel amplicon‐based next‐generation sequencing method, CLAmp‐seq (circular ligation amplification and sequencing), with median detection rate of 100% (MAF = 0.1%, input = 20 ng). CLAmp‐seq readouts demonstrate strong concordance with droplet digital PCR (ddPCR) (97.4%) and tissue amplification refractory mutation system PCR (ARMS‐PCR) (94.8%) in pretreatment patients.